STYLISTIC CORRESPONDENCE IN LITERARY TRANSLATION IS ONE OF THE STYLISTIC DEVICES IN THE EXAMPLE OF SIMILE (Scientific journal of the Fergana State University, 2024)
Translation of a literary text into another language is considered one of the most difficult tasks, especially the transfer of stylistic devices while preserving the writer’s style requires sufficient knowledge from the translator. One of the main tasks of this article was to analyse the stylistic correspondence that occurs in the process of literary translation on the example of a simile, which is one of the stylistic devices. In addition, this article reveals one of the types of semantic-stylistic transformation, addition in the translation process. The analysis includes excerpts from the story “Shimol oddiseyasi” by Jack London. This story was presented to Uzbek readers through Russian by the Uzbek translator F.Abdullayev. The results of the analysis show that typologies of stylistic events can be seen stylistic correspondence, stylistic substitution, stylistic amplification and stylistic weakening